Human cells can adaptively evolve to hypomorphic mutations in an essential gene of the nuclear pore complex - Targa, Altea (Nanyang Technological University, 2021)
Adaptive evolution in response to cellular stress is a critical process implicated in a wide range of core biological and clinical phenomena, including emergence of drug resistance. While it is now widely accepted that single-celled organisms can rapidly adapt to selective pressure, we still lack understanding of the processes that drive this remarkable ability in human cells. To uncover such mechanisms, in this thesis hypomorphic alleles of the essential nuclear pore complex (NPC) gene NUP58 were generated. By dissecting both early and long- term mechanisms of adaptation in independent clones, I observed that early adaptation might correlate with transcriptional changes and upregulation of molecules known to interact with the NPC. In contrast, long-term adaptation occurred via focal amplification of NUP58 and restoration of mutant protein expression. These data support the concept that transient physiological changes predate and favour a later refined genetic adaptation. Targeting both mechanisms in parallel may improve combinatorial therapeutic approach to prevent development of drug resistance.